An exploration into regional variation in innovative activity in China. (1st January 2001) - Liu, Xielin; White, Steven
Based on Chinese patent data from the period 1985-95, this paper explores regional variation in innovative activity and performance. Preliminary analyses suggest that regional differences in economic activity and innovation inputs - personnel and funding - are closely related to differences in patenting activity. However, the results also suggest that personnel may be the most important factor. The data also suggest that regions are undergoing important changes in technological specialisation, although the eventual impact on economic performance and competitiveness is not yet clear.